2020
DOI: 10.3390/ijms21186854
|View full text |Cite
|
Sign up to set email alerts
|

Deoxypodophyllotoxin, a Lignan from Anthriscus sylvestris, Induces Apoptosis and Cell Cycle Arrest by Inhibiting the EGFR Signaling Pathways in Esophageal Squamous Cell Carcinoma Cells

Abstract: Deoxypodophyllotoxin (DPT) derived from Anthriscus sylvestris (L.) Hoffm has attracted considerable interest in recent years because of its anti-inflammatory, antitumor, and antiviral activity. However, the mechanisms underlying DPT mediated antitumor activity have yet to be fully elucidated in esophageal squamous cell carcinoma (ESCC). We show here that DPT inhibited the kinase activity of epidermal growth factor receptor (EGFR) directly, as well as phosphorylation of its downstream signaling kinases, AKT, GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…95 In 2020, Kwak found the DPT-induced G2/M phase arrest and apoptosis of ESCC cells by inhibiting the epidermal growth factor receptor (EGFR) mediated AKT/ERK signalling pathway. 96 To overcome the resistance to inhibitors of the epidermal growth factor receptor (EGFR), which is related to the hepatocyte growth factor receptor MET, for targeted therapy of cancer. In 2021, Kim used DPT to treat non-small cell lung cancer (NSCLC) and found that DPT could suppress the expression of p -EGFR and p-MET as well as their downs treat proteins p -ErbB3, p -AKT, and p -ERK, and induced high ROS generation.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…95 In 2020, Kwak found the DPT-induced G2/M phase arrest and apoptosis of ESCC cells by inhibiting the epidermal growth factor receptor (EGFR) mediated AKT/ERK signalling pathway. 96 To overcome the resistance to inhibitors of the epidermal growth factor receptor (EGFR), which is related to the hepatocyte growth factor receptor MET, for targeted therapy of cancer. In 2021, Kim used DPT to treat non-small cell lung cancer (NSCLC) and found that DPT could suppress the expression of p -EGFR and p-MET as well as their downs treat proteins p -ErbB3, p -AKT, and p -ERK, and induced high ROS generation.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…DNA damage and cell cycle can lead to irreversible cell cycle arrest, which induces cell apoptosis. Researchers have shown that regulation of key cell cycle proteins can induce cell cycle arrest in ESCC cells and produce anti-tumor effects ( Yao et al, 2015 ; Kwak et al, 2020 ). Prior research has shown that CUR induces cell cycle arrest in cells of acute myeloid leukemia ( Zhou et al, 2021 ), colorectal cancer cells ( Li et al, 2021 ), and pancreatic cancer cells ( Zhu and Bu, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We further provided the evidence of significant changes of the key factors involved in these pathways upon CR treatment by western blotting. In fact, mounting evidence has shown that inhibition of Akt/ERK pathways can lead to cell cycle arrest or apoptosis [25][26][27][28][29][30]. For example, a recent study showed that inhibition of Akt/ERK pathways by Hedyotis diffusa Willd (HDW) extracts could induce apoptosis in glioblastoma [25].…”
Section: Discussionmentioning
confidence: 99%